PATRIARKI DALAM KITAB SUCI YANG TERKOMODIFIKASI - Luthfillah, Muhammad Dluha (SUHUF, 2019)
Al-Qurâ€™an Terjemahan Wanita constitutes a part of what I call the commodified mushaf, a contemporary Qurâ€™anic phenomenon characterized by its â€œnew outlookâ€, new calligraphyâ€“ including the coloring of the words and clauses â€“ and new variation of additional text. Closely reading the paratext of Al-Qurâ€™an Terjemahan Wanita Cordoba, I find five points of patriarchal and conservative narrative. Source criticism to the texts reveals that these narratives are derived, and often cited, from the works of central figures of certain Islamist movements. This shows at least two things. First, the assumption of women as consumer niche brings with itself an underlying supposition that women can never be detached from the so-called commodity fetishism. The very supposition explains why the Quran for women must have a number of additional features and has to be that â€˜stylishâ€™. Second, the emergence and distribution of such conservative paradigm is of consequences brought about by the intersection of Islam and consumerism, of religion and capitalism. It constitutes the locus in which marketization and conventional (not to say conservativeliteralist) Gender paradigm converge, and thus corresponds to sociologists arguing that such intersection would only produce and further distribute conservative views on the Islamic authority. This article offers a new way of research on the keywords woman and Quran, extending the scope beyond the questions on the meaning of Quranic verses and thoughts of Muslim and non-Muslim thinkers.